Sustained thymopoiesis and improvement in functional immunity induced by exogenous KGF administration in murine models of aging. - Min, D; Panoskaltsis-Mortari, A; Kuro-O, M; Holländer, G; Blazar, B; Weinberg, K (2007)
Age-related thymopoietic insufficiency has been proposed to be related to either defects in lymphohematopoietic progenitors or the thymic microenvironment. In this study, we examined whether keratinocyte growth factor (KGF), an epithelial cell-specific growth factor, could increase thymopoietic capacity in aged mice by restoration of the function of thymic epithelial cells (TECs). The thymic cellularity in KGF-treated aged mice increased about 4-fold compared to placebo-treated mice, resulting in an equivalent thymic cellularity to young mice. Enhanced thymopoiesis was maintained for about 2 months after a single course of KGF, and sustained improvement was achieved by administration of monthly courses of KGF. With the enhanced thymopoiesis after KGF treatment, the number of naive CD4 T cells in the periphery and T-cell-dependent antibody production improved in aged mice. KGF induced increased numbers of TECs and intrathymic interleukin-7 (IL-7) production and reorganization of cortical and medullary architecture. Furthermore, KGF enhanced thymopoiesis and normalized TEC organization in klotho (kl/kl) mice, a model of premature degeneration and aging, which displays thymopoietic defects. The result suggests that TEC damage is pathophysiologically important in thymic aging, and KGF therapy may be clinically useful in improving thymopoiesis and immune function in the elderly.